Gemini - Němcová, Hana (Vysoké učení technické v Brně. Fakulta architektury, 2024)
Cílem návrhu je vytvořit příjemné a funkční prostředí pro studium a pobyt mládeže se zdravotním znevýhodněním ve Střední škole GEMINI. Požadavek k navýšení počtu dětí je také důvodem nejen revitalizace a modernizace stávající budovy, ale i novostavby další budovy. Dalším hlediskem projektu je vhodné začlenění stavby do prostředí sídliště Brno – Lesná.

The goal of the proposal is to create a pleasant and functional environment for study and stay of youth with a medical disadvantage in the GEMINI Secondary School. Requirement the reason for the increase in the number of children is not only revitalization and modernization existing buildings, but also new constructions of other buildings. Another aspect of the project is the appropriate integration of the building into the environment of the housing estate Brno – Lesná.
Gemini
Keywords: GEMINI; střední škola; internát; bezbariérovost; GEMINI; high school; boarding school; accessibility